Intencionalidade da consciência e ação educativa em Sartre: por uma pedagogia da liberdade - Viana, Cláudio Pires (2019)
This study is part of the Line of Research Education Fundaments and Educational Processes of the Graduate Course Program in Education of Federal University of Goias. The idea of the intentionality of consciousness, basic concept of the Edmund Husserl’s phenomenology and settled for Jean-Paul Sartre [1905-1980], rigorously overcome any duality that tries to enforce the relation between the consciousness and the world. As of the argument that “every consciousness is consciousness of something”, the pure concept of world, of objective reality, separated from the subjectivity, is no more than an abstraction as well as the concept of the individual separated from the world and its coefficients of adversity. Man and world cannot be considered autonomic, independent and non-reciprocal entities. In fact, they are two dimensions that are totally inseparable, despite of being different in essence. By intentionality, consciousness and world they form a totality, they constitute each other mutually. With these assumptions, this thesis proposes to investigate the sense of education, its nature, foundation and purposes, apart from the empirical, the common sense and the natural attitude. Although Sartre has not elaborated any study or theory about this issue, we understand that his philosophical work can help us to think about the education as an essentially human phenomenon, its ontological sense, as a permanent movement of the formation and constitution of the man, ánthrõpos, in the relation between the consciousness and the world. Therefore, we seek to clarify and to deepen the comprehension and foundations of a conception of education that will contribute for the constitution of the subject in a humanizing perspective, in opposition to the instrumentalist visions that aim to attend the interests of the capital, consumption, market and efficiency. For this purpose, we propose to investigate the intentionality and action concepts in the Sartre’s work, establishing a relation with educational phenomenon and emphasizing its being as something inherent in the paradox of freedom: there is no education except in situation, and there is no situation except in freedom. Educating is the action of being free, considering the several dimensions of human formation posted by the relationof man with the world in time, implying the totality of being and existence that forms an inseparable synthetic unity and affirms dignity and the sense of knowledge, of corporeity, of imagination, of emotion, of desire, of temporality, of historicity, of spatiality and of intersubjectivity as intrinsic expressions of human reality in constant formation.